Design system of exchange dies for stamping small press 110 t machines to achieve SMED / Muhamad Hanafi Ghazali - Ghazali, Muhamad Hanafi (2009)
Single Minute Exchange of Dies (SMED) is basically a methodology for systematic and radical reduction of setup times, with documented cases reductions from hours to less than ten minutes (single digit minutes). Consequently, they are widely used in industrial companies to manage exchange dies activity with cost effective, utilization of time, minimize manpower and equipment. This project presents an optimum design of SMED for Autokeen Sdn.Bhd to replace the current small press production lines exchange dies system. Several improvement steps are being applied throughout the project to measure the impact from redesigning the current system. The results from improvement are being compared to the current system in terms of downtime, and percentage of reduction.